Polyphenol-Gated Composite Electrolytes with Enhanced Cross-Phase Lithium-Ion Transport for Solid-State Lithium Batteries - Li, Xiaoxiao; Jiang, Minqiang; Chen, Kai; Cai, Zhixiang; Zhang, Yingxin; Luo, Jiamei; Hou, Lei; Zhou, Yazhou; Zhang, Chao; Zhang, Hui; Lai, Feili; Miao, Yue‑E; et al. (Nano-Micro Letters, 2026)
Solid-state lithium (Li) batteries offer high-energy density and operational safety but face sluggish Li+ transport in polymer/ceramic composite solid-state electrolytes. Herein, we propose a bioinspired polyphenol-gated interfacial engineering that mimics ion-selective protein channels to enhance Li+-selective transport across the polymer–ceramic interface. Polyphenols such as polydopamine, poly-tannic acid, and poly-gallic acid chemically couple La0.56Li0.33TiO3 ceramic nanofibers and glycidyl polyether matrix. Within this interface, carbonyl groups selectively coordinate Li⁺ and facilitate directional migration. On the other hand, hydroxyl and amino groups immobilize anions via hydrogen bonding. This chemical gating nearly doubles interfacial Li+ concentration and boosts transference number to 0.68. The corresponding Li||LiFePO4 battery exhibits stable cycling over 600 cycles with 85.5% capacity retention at 1 C, while the pouch cell delivers reliable operation under mechanical stress caused by bending and puncturing. This work demonstrates that polyphenol-gated interfaces are essential for promoting selective and efficient cross-phase Li⁺ transport for high-performance solid-state lithium-metal batteries. Highlights: 1 A biomimetic polyphenol-gated strategy is proposed to promote interfacial Li+ - selective transport in composite solid electrolytes by chemically bonding the polymer matrix and ceramic nanofibers. 2 The polyphenol interlayers serve as the chemical gates with –OH and –NH groups to immobilize lithium salt anions and carbonyl groups to coordinate Li+, thus lowering the energy barrier and promoting rapid Li+ transport at interface. 3 The assembled Li||LiFePO4 batteries exhibits an impressive capacity of 151.6 mAh g−1 and long lifespan over 600 cycles.